2013
DOI: 10.1371/journal.pone.0085476
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Retardation and Conserved miRNAs Are Correlated to Hibiscus Chlorotic Ringspot Virus Infection

Abstract: Virus infection may cause a multiplicity of symptoms in their host including discoloration, distortion and growth retardation. Hibiscus chlorotic ringspot virus (HCRSV) infection was studied using kenaf (Hibiscus cannabinus L.), a non-wood fiber-producing crop in this study. Infection by HCRSV reduced the fiber yield and concomitant economic value of kenaf. We investigated kenaf growth retardation and fluctuations of four selected miRNAs after HCRSV infection. Vegetative growth (including plant height, leaf si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 32 publications
2
17
2
Order By: Relevance
“…In this study, we report an almost three‐fold reduction in miR156, miR171 and miR167 after CPsV infection. Some of their target transcripts ( SPL s, SCL s and ARF s) have been reported previously to be related to symptom expression and defence (Gao et al ., ; Jay et al ., ; Padmanabhan et al ., ). In the present study, we found that SPL s and SCL were concomitantly up‐regulated in CPsV‐infected plants, but could not find a general correlation between the expression patterns of all the assessed miRNA target transcripts with the two types of exhibited symptom or with one of the two distant CPsV isolates.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we report an almost three‐fold reduction in miR156, miR171 and miR167 after CPsV infection. Some of their target transcripts ( SPL s, SCL s and ARF s) have been reported previously to be related to symptom expression and defence (Gao et al ., ; Jay et al ., ; Padmanabhan et al ., ). In the present study, we found that SPL s and SCL were concomitantly up‐regulated in CPsV‐infected plants, but could not find a general correlation between the expression patterns of all the assessed miRNA target transcripts with the two types of exhibited symptom or with one of the two distant CPsV isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco plants inoculated with tobacco mosaic virus and tomato mosaic virus showed severe symptoms and displayed an increase in miR156, miR159, miR160, miR164, miR166, miR169, and miR171 (Bazzini et al 2007). In addition, kenaf (Hibiscus cannabinus L.) showed severely disrupted vascular bundles and displayed greater fluctuations of miR171 and miR168 and their targets SCL1 and AGO1 after Hibiscus chlorotic ringspot virus infection (Gao et al 2013). When transgenic Arabidopsis and Brassica were infected with viruses, miR156, miR158, miR160, miR162, miR164, and miR1885 were highly upregulated after inoculation for 10-15 days (Kasschau et al 2003;He et al 2008).…”
Section: Effect Of Cymmv Infection On Mirna Expressionmentioning
confidence: 99%
“…Viruses are economically important plant pathogens that typically cause symptoms of yellowing, mosaic, twisting and even necrosis of leaves, and plant death in many cases. Studies with many different viruses have shown that virus‐infected plants generally have a changed expression profile of miRNAs (Abreu et al ., ; Amin et al ., ; Bazzini et al ., ; Chen et al ., , ; Cillo et al ., ; Du et al ., ; Feng et al ., , ; Guo et al ., ; Lang et al ., , ; Liu et al ., ; Naqvi et al ., ; Pradhan et al ., ; Sun et al ., ; Wang et al ., ; Xu et al ., ; Yang et al ., ) and, in some cases, these changes are associated with viral symptoms (Gao et al ., ; Lian et al ., ; Romanel et al ., ). Bazzini et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite this well‐established correlation, there is little direct experimental evidence linking changed expression of particular miRNAs to viral symptoms (Gao et al ., ; Lian et al ., ; Romanel et al ., ). Recently, we reported that a reduction in osa‐miR171b in Rice stripe virus (RSV)‐infected rice contributed to RSV symptoms (Tong et al ., ).…”
Section: Introductionmentioning
confidence: 99%